2008
DOI: 10.1074/mcp.m700525-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Pigment Epithelium Lipofuscin Proteomics

Abstract: Lipofuscin accumulates with age in the retinal pigment epithelium (RPE) in discrete granular organelles and may contribute to age-related macular degeneration. Because previous studies suggest that lipofuscin contains protein that may impact pathogenic mechanisms, we pursued proteomics analysis of lipofuscin. The composition of RPE lipofuscin and its mechanisms of pathogenesis are poorly understood in part because of the heterogeneity of isolated preparations. We purified RPE lipofuscin granules by treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
152
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(154 citation statements)
references
References 38 publications
1
152
0
1
Order By: Relevance
“…Of course other oxidative protein modifications accumulate in the eye with age and possibly contribute to AMD pathogenesis. Such modifications include advanced glycation end products in the choriocapillaris, Bruch membrane, and CNV membranes (29,30) and nitrotyrosine and iso [4]levuglandin E 2 adducts (as well as CEP adducts) in RPE lipofuscin granules (31). Why ocular tissues in AMD patients are more susceptible to oxidative damage than normal eye tissue remains to be determined, but oxidative markers formed from retina-rich components like DHA lipids offer a potential early warning system for predicting AMD susceptibility.…”
Section: Amd Risk Genotypementioning
confidence: 99%
“…Of course other oxidative protein modifications accumulate in the eye with age and possibly contribute to AMD pathogenesis. Such modifications include advanced glycation end products in the choriocapillaris, Bruch membrane, and CNV membranes (29,30) and nitrotyrosine and iso [4]levuglandin E 2 adducts (as well as CEP adducts) in RPE lipofuscin granules (31). Why ocular tissues in AMD patients are more susceptible to oxidative damage than normal eye tissue remains to be determined, but oxidative markers formed from retina-rich components like DHA lipids offer a potential early warning system for predicting AMD susceptibility.…”
Section: Amd Risk Genotypementioning
confidence: 99%
“…The RPE is responsible for generating vitamin A derivatives required for phototransduction, the initial steps of vision, through a series of biochemical reactions called the visual cycle. Byproducts of the visual cycle are thought to aggregate in the lysosomal compartment of the RPE [12] as lipofuscin, which has an intense fluorescent signal [13][14][15]. Because this signal comes from endogenous substances, rather than exogenously introduced fluorescent markers, it is referred to as lipofuscin autofluorescence (AF).…”
Section: Application: Fluorophore Signal Recovery In the Human Rpementioning
confidence: 99%
“…Surprisingly, only 12 proteins (11%) of Warburton's list were common with the 65 proteins identiied by Schut et al This discrepancy probably results from variations in the purity of sucrose-isolated granules [33] and from the fact that lipofuscin proteins are microheterogeneous in size due to abundant oxidative modiications while contaminant proteins are intact and therefore, run as well-focused spots. In a third study, Ng et al [34] analyzed the composition of highly puriied RPE-lipofuscin granules devoid of Lysosomes -Associated Diseases and Methods to Study Their Functionmembranes and reported that the luminal material was 98% lipids, mostly LBs [35]. Taking all this information into account, the current concept is that RPE lipofuscin originates from LBs in photoreceptors and is transferred to RPE lysosomes during POS phagocytosis.…”
Section: Rpe Lipofuscin Accumulationmentioning
confidence: 99%